The Role of Community Beliefs and Practices on the Spread of Ebola in Uganda, September 2022 - Helen Nelly Naiga; Jane Frances Zalwango; Brian Agaba; Saudah N. Kizito; Brenda N. Simbwa; Maria Goretti Zalwango; Rebecca Akunzirwe; Zainah Kabami; Peter Chris Kawugenzi; Robert Zavuga; Mackline Ninsiima; Patrick King; et al. (Journal of Epidemiology and Global Health)
Abstract Background On September 20, 2022, Uganda declared an Sudan Virus Disease (SVD) outbreak in Mubende District. Another eight districts were infected September–November 2022. We examined how Ugandan community beliefs and practices spread Sudan Ebola Virus (SUDV) in 2022. Methods A qualitative study was conducted in Mubende, Kassanda, and Kyegegwa districts in February 2023. Nine focus group discussions and six key informant interviews were held. We investigated whether community beliefs and practices contributed to spreading Sudan Ebola Virus (SUDV). Interviews were recorded, translated, transcribed, and thematically analyzed. Results The community deaths, later found to be due to Sudan Virus Disease(SVD), were often attributed to witchcraft or poisoning. Key informants reported that SVD patients often sought traditional healers or spiritual leaders before or after formal healthcare failed. They also found that traditional healers treated SVD patients without precautions. Religious leaders praying for SVD patients and their symptomatic contacts, SVD patients hiding in friends’ homes, and exhuming SVD patients from safe and dignified burials to allow traditional burials were other themes. Conclusion Diversity in community beliefs and culture likely contributed to spreading the 2022 Ugandan SVD outbreak. Public health systems, traditional healers, and religious leaders can help Uganda control ebolavirus outbreaks by identifying socially acceptable and scientifically supported infection control methods.